2004
DOI: 10.1128/jcm.42.1.264-268.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bartonella henselae in Italian Stray Cats: Evaluation of Serology To Assess the Risk of Transmission of Bartonella to Humans

Abstract: Bartonella henselae is the major etiological agent of cat scratch disease in humans. Cats act as the natural reservoir of B. henselae and can transmit the infection to humans by a bite or scratch. The prevalence of B. henselae in cat populations was evaluated by serological and bacteriological tests. A total of 769 stray cats from three urban and three rural areas in northern Italy were sampled between January 1999 and December 2000. The positive and the negative predictive values of serological tests with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
50
0
3

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 22 publications
9
50
0
3
Order By: Relevance
“…Seroprevalence in cats varies from 14 to 50 % across studies, and it has been reported that cats may have persistent and asymptomatic bacteremia (Koehler et al 1994, Baneth et al 1996, Bergmans et al 1997, Chomel et al 1999, 2006a, b, Hjelm et al 2002, Fabbi et al 2004. A study by Slhessarenko et al (1996) on the seroprevalence of cats in the city of São Paulo, Brazil, revealed 46% sero-reactivity to Bartonella spp.…”
Section: Seroepidemiologic Studiesmentioning
confidence: 99%
“…Seroprevalence in cats varies from 14 to 50 % across studies, and it has been reported that cats may have persistent and asymptomatic bacteremia (Koehler et al 1994, Baneth et al 1996, Bergmans et al 1997, Chomel et al 1999, 2006a, b, Hjelm et al 2002, Fabbi et al 2004. A study by Slhessarenko et al (1996) on the seroprevalence of cats in the city of São Paulo, Brazil, revealed 46% sero-reactivity to Bartonella spp.…”
Section: Seroepidemiologic Studiesmentioning
confidence: 99%
“…Both genotypes are present worldwide, but the Marseille genotype appears to be dominant in the European cat population, whereas the Houston-1 genotype is more common in Asia (7). However, the relative prevalence of the two genotypes in felines also shows regional variations (23,31,33).…”
mentioning
confidence: 99%
“…Επιζωοτιολογικές μελέτες διεςήχθηκαν κυρίως σε κλινικά υγιείς γάτες (κατοικίδιες και αδέσποτες) και αφορούσαν αφενός στη συχνότητα λοίμωξης με την άμεση ανίχνευση του βακτηρίου, κυρίως σε καλλιέρ γειες αίματος, η οποία στη συνέχεια επιβεβαιώθηκε με τη βοήθεια μοριακών μεθόδων (PCR-RFLP) ταυ-τοποιώντας παράλληλα το υπεύθυνο είδος, στέλεχος και γενότυπο του βακτηρίου (Chomel et al 1995, Bergmans et al 1997, Heller et al 1997, Sander et al 1997, Chomel et al 1999, Marston et al 1999, Arvand et al 2001, Chomel et al 2002, La Scola et al 2002, Avidor et al 2004, Engback et al 2004, Fabbi et al 2004, Rolain et al 2004, Crissiuma et al 2011 και αφετέρου στη συχνότητα έκθεσης στο βακτήριο με την ανίχνευση ειδικών αντισωμάτων με ορολογι κές εξετάσεις (έμμεσος ανοσοφθορισμός και ELISA) (Al-Majali, 2004, Baneth et al 1996, Bergmans et al 1997, Childs et al 1995, Chomel et al 1995, Chomel et al 1999, Chomel et al 2002, Crissiuma et al 2011, Ebani et al 2002, Glaus et al 1997, Fabbi et al 2004, Gurfield et al 2001, lljclm et al 2002, Kelly et al 1996, Leighton et al 2001, Maruyama et al 2003, Nutter et ah 2004, Podsiadly et al 2003, SolanoGallcgo et al 2006, Ueno et al 1995.…”
Section: äEaomenaunclassified
“…Στην Ευρώπη και τη Βόρεια Αμερική επικρατεί ο γενότυπος Marseille type 11 της Β. henselae (Birtlcs et al 2002, Chomel et al 2002, Fabbi et al 2004, Montcil et al 2007), ενώ στην Ασία ο Houston 1 (type I) (Chomel et al 1999, Maruyama et al 2000, Maruyama et al 2001). …”
Section: äEaomenaunclassified
See 1 more Smart Citation